THE EFFECT OF WATER CONTENT OF RAW MATERIALS ON DRYING RATE AND YIELD OF LEMON PEEL EXTRACTION AS AN ESSENTIAL OIL FOR MANUFACTURING NATURAL PERFUME - Winaliani, Winaliani; Myra Wardati Sari (Prodi Kimia, 2024)
Lemon peel can be used as a raw material in making products such as natural perfume because it contains limonene compounds, which can provide a refreshing aroma. This research aimed to determine the effect of raw material moisture content on the drying rate and extraction yield of lemon peel as an essential oil for making natural perfume. The method employed in this research is soxhlet extraction with variations in the mass of lemon peel, namely 120 grams and 150 grams, and variations in drying time, namely 120 minutes and 150 minutes, and variations in the extraction time carried out are 150 minutes and 170 minutes using 70% ethanol solvent. This research was carried out in two stages, drying and extraction. The best drying results were obtained by sample A3, which had a sample mass variation of 120 grams and a drying time of 150 minutes. The best extract yield was obtained by sample A3, which had a sample variation of 120 grams, a drying time of 150 minutes, and an extraction time of 170 minutes.